Nutrisi pada Penderita Kanker Paru : [Nutrition Management in Lung Cancer Patients] - Risnawati Risnawati; Isnu Pradjoko; Farah Fatma Wati (Faculty of Medicine Universitas Airlangga, 2019)
World Health Organization data shows that lung cancer is the leading cause of death in the group of deaths due to malignancy. Weight loss is common in lung cancer. Known side effects of chemotherapy and those that affect nutritional status include anorexia, nausea, vomiting, satiety and mucositis. In total 40-60% of lung cancer patients experience unintentional weight loss. Weight loss and reduced nutritional status have been identified as negative prognostic variables for patients. Nutritional disorders during chemotherapy if left untreated can cause interference and delay treatment. Therefore there is a need for nutritional management in patients with lung cancer so that treatment runs smoothly and supports patient health.